Study on the incidence and related risk factors for impulsive control disorders in Parkinson's disease - XIE Xin; LUO Xiao⁃guang; CHEN Rong⁃jie (Chinese Journal of Contemporary Neurology and Neurosurgery, 2021)
Objective To investigate the incidence and risk factors for impulsive control disorders (ICDs) in Parkinson's disease (PD). Methods A total of 201 patients with PD were included from May 2016 to September 2017. ICDs were assessed by Questionnaire for Impulsive⁃Compulsive Disorders in Parkinson's Disease (QUIP). Mentation, behavior and mood, activities of daily living, motor function, and complications for therapy were assessed by Unified Parkinson's Disease Rating Scale (UPDRS). Disease severity was assessed by Hoehn⁃Yahr staging, and depression was assessed by Geriatric Depression Scale (GDS). Univariate and multivariate forward Logistic regression analyses were used to analyze the risk factors for PD patients with ICDs. Results Among 201 PD patients, 41 patients (20.40%) were diagnosed with ICDs, including 17 cases of compulsive medicine use (8.46%), 15 cases of compulsive eating (7.46%), 13 cases of punding (6.46%), 8 cases of compulsive shopping (3.98%), 3 cases of pathological gambing (1.49%) and one case of hypersexuality (0.49%). Logistic regression analysis showed that the longer treatment duration (OR=1.237, 95%CI: 1.038-1.474; P=0.018), severe complications for therapy (high UPDRS Ⅳ score; OR=1.389, 95%CI: 1.077-1.790, P=0.011), depression (OR=2.417, 95%CI: 0.174-0.984; P=0.046) were the risk factors for PD patients with ICDs. Conclusions The incidence of ICDs in PD is high, which is affected by many factors. The risk of ICDs can be evaluated by the QUIP scale to guide medication.